The potential value of miR-1 and miR-374b as biomarkers for colorectal cancer - Wu, Xiaobing (Int J Clin Exp Pathol, 2015)
The mortality of colorectal cancer (CRC) is growing due to the unsatisfactory specificity and sensitivity of the existing screening methods. Previous studies have focused on the role of miRNAs as CRC biomarkers. However, few studies have examined the miRNA profiles at each stage. The objective of this study was to identify miRNAs that distinguish CRC patients from normal people to prevent the misdiagnosis of patients with certain stages of CRC. We performed miRNA profiling of 1547 human miRNAs by qRT-PCR in CRC patients with stage II and stage III disease. The statistical analyses showed that there were 96 miRNAs that were significantly dysregulated in CRC relative to normal tissues (P<0.05). There were 28 dysregulated miRNAs associated with separate or combined stages II and III disease. There were 25 downregulated miRNAs, including the following: miR-1, -145, -145*, -137, -363, -143, -4770, -490-5p, -9, -144*, -99a, -99b, -23b, -143*, -100, -768-3p, -24-1*, -125a-5p, -30e*, -574-3p, -126, let-7b, miR-1979, -374b, and -140-3p. We found an upregulation of miR-203, 182, and 96. Our results demonstrated that the expression of miR-1 and miR-374b was significantly decreased in each stage and may function as a biomarker of CRC. Furthermore, 20 miRNAs were dysregulated both in stage II disease without lymph node or distant metastasis and in stage II-III tumors but not in stage III tumors. Only miR-4794 was involved exclusively with stage II tumors, and there were 19 miRNAs that were dysregulated only in stage III disease with lymph node metastasis and in stage II-III disease. There were only 6 miRNAs that were uniquely dysregulated in stage III. Our results indicate that miRNA expression may be valuable in the clinic. However, large prospective studies are required to confirm the role of miRNAs. This study provides a new model for analyzing novel CRC biomarkers by considering more clinical factors.